KOMPOSISI GIZI DAN DAYA TERIMA MAKANAN TERAPI: READY TO USE THERAPEUTIC FOOD UNTUK BALITA GIZI BURUK (NUTRITION COMPOSITION AND ACCEPTANCE TEST OF READY TO USE THERAPEUTIC FOOD FOR SEVERE MALNOURISHED CHILDREN) - Komari Komari; Astuti Lamid (Persagi, 2012)
Abstract Severe malnourished children need special diet which is nutritious, easily digested, and safe to improve their nutritional status. The diet could be Ready-to-Use Therapeutic Food (RUTF), composed by highly digestible component such as milk, vegetable oil, sugar, vitamines, minerals, and indigenous food such as peanut, mungbean and tempeh powder. This study was aimed to examine the nutrients content and the sensory quality of local RUTF. The method utilised were acceptability test on severe malnourished children, chemical analyses to identify nutrient content and safety analysis towards microbial and heavy metal contaminants. The results showed that RUTF contained energy ranging from 521 kcal /100 g to 530 kcal/100 g, and protein ranging from 14,1 g/100 g to 16,9 g/100g. The RUTF was acceptable by malnourished children under five years old. Keywords: ready to use, therapeutic food, malnourished Abstrak Anak gizi buruk memerlukan diet yang khusus untuk meningkatkan status gizinya dengan makanan yang mudah dicerna, bergizi tinggi dan aman. Makanan tersebut dapat berupa Ready to Use Therapeutic Food (RUTF) yang terdiri dari bahan yang mudah dicerna seperti susu, minyak sayur, gula, vitamin dan mineral, dan menggunakan bahan makanan lokal yakni tepung kacang tanah, kacang hijau, dan tempe. Penelitian ini bertujuan menilai komposisi zat gizi dan kualitas sensori produk RUTF lokal. Metode yang digunakan adalah uji daya terima yang dilakukan terhadap anak balita gizi buruk, uji kimia untuk mengukur komposisi gizi dan keamanan terhadap mikroba dan logam berat. Hasil menunjukkan bahwa komposisi gizi untuk RUTF mengandung cukup tinggi energi yaitu berkisar antara 521-530 kkal/100g dan protein berkisar antara 14,1-16,9 g/100g. Makanan tersebut juga dapat diterima oleh anak-anak balita gizi buruk. [Penel Gizi Makan 2012, 35(2): 159-167] Kata Kunci: ready to use, makanan terapi, gizi buruk